Chronic Toxoplasma infection modifies the structure and the risk of host behavior. - Cristina Afonso; Vitor B Paixão; Rui M Costa (PLoS ONE)
The intracellular parasite Toxoplasma has an indirect life cycle, in which felids are the definitive host. It has been suggested that this parasite developed mechanisms for enhancing its transmission rate to felids by inducing behavioral modifications in the intermediate rodent host. For example, Toxoplasma-infected rodents display a reduction in the innate fear of predator odor. However, animals with Toxoplasma infection acquired in the wild are more often caught in traps, suggesting that there are manipulations of intermediate host behavior beyond those that increase predation by felids. We investigated the behavioral modifications of Toxoplasma-infected mice in environments with exposed versus non-exposed areas, and found that chronically infected mice with brain cysts display a plethora of behavioral alterations. Using principal component analysis, we discovered that most of the behavioral differences observed in cyst-containing animals reflected changes in the microstructure of exploratory behavior and risk/unconditioned fear. We next examined whether these behavioral changes were related to the presence and distribution of parasitic cysts in the brain of chronically infected mice. We found no strong cyst tropism for any particular brain area but found that the distribution of Toxoplasma cysts in the brain of infected animals was not random, and that particular combinations of cyst localizations changed risk/unconditioned fear in the host. These results suggest that brain cysts in animals chronically infected with Toxoplasma alter the fine structure of exploratory behavior and risk/unconditioned fear, which may result in greater capture probability of infected rodents. These data also raise the possibility that selective pressures acted on Toxoplasma to broaden its transmission between intermediate predator hosts, in addition to felid definitive hosts.